Project manager competencies associated with the projects' success in the public sector. - Lemos Dias, Taciana (2023)
Although project management is widely used in the public sector, many projects still fail even when project management tools and practices are employed. Several studies show that a project's success depends partly on the project manager's competencies; however, there is little empirical research on this subject in the public sector. This study aims to analyze the significant characteristics linked with the competencies of the public sector project manager and outlines a profile of these professional competencies characteristics that can lead to the success of projects. Through empirical research conducted with 77 project managers from 32 public organizations in Brazil, this study examined the relationship between project managers' competencies and the likelihood that projects will succeed. Using factor analysis and logistic regression, we looked at factors like time, cost, quality, and scope to determine their relationship to the likelihood that projects will succeed. The findings highlight the importance of project management knowledge, communication abilities, attitudes relating to motivation, trust, and emotional intelligence, and most traits defining project managers in the public sector. The employee's length of service was the single factor that had a negative impact on the project's outcomes. This study contributes to the current knowledge of project managers' competencies in the public sector, showing the main characteristics a successful project manager needs to have and can help direct efforts in selecting a more suitable professional, contributing to the reduction of the turnover of the workforce and the consequent loss of knowledge of the organization.